PERANAN SEKTOR INDUSTRI PENGOLAHAN DALAM PEREKONOMIAN INDONESIA: MODEL INPUT-OUTPUT - Azzely Muhammad Hilman; Astrid Maria Ester (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
This study aims to analyze the role of the manufacturing industry in the economy in Indonesia. This study analyzes the linkages of the manufacturing industry sector with other economic sectors, both for input providers and sectors that use output from the manufacturing industry in Indonesia. this study also analyzes the dispersion coefficients and the sensitivity of the spread of the processing industry sector, and analyzes the economic effects caused by the manufacturing industry sector based on the multiplier effect on the labor force. The analytical method used is an analysis of the 2015 Indonesia Input-Output Table with a classification of 17 sectors. Based on the results of data processing, on the linkage analysis, forward linkage the manufacturing sector is relatively larger compared with the backward linkage, as well as the manufacture industry has the highest direct forward linkage to the construction sector and the manufacture industry has the highest direct backward linkage to the industrial sectors processing itself. On the value of spread coefficient is obtained that the manufacturing industry sector is able to increase the growth of the upstream sector and at deployment sensitivity index shows the results of the manufacturing industry sector can also be able to increase growth in the downstream sector. In terms of labor multiplier, Overall if the final demand of the manufacturing industry sector is increased by 1%, it will increase the total employment opportunity of Indonesia in 2010 by 202,860 people or increase by 1,278% from the previous amount.